2000
DOI: 10.1046/j.1432-1327.2000.01451.x
|View full text |Cite
|
Sign up to set email alerts
|

Phytanoyl‐CoA hydroxylase activity is induced by phytanic acid

Abstract: Phytanic acid (3,7,11,15-tetramethylhexadecanoic acid) is a branched-chain fatty acid present in various dietary products such as milk, cheese and fish. In patients with Refsum disease, accumulation of phytanic acid occurs due to a deficiency of phytanoyl-CoA hydroxylase, a peroxisomal enzyme containing a peroxisomal targeting signal 2. Recently, phytanoyl-CoA hydroxylase cDNA has been isolated and functional mutations have been identified. As it has been shown that phytanic acid activates the nuclear hormone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 30 publications
1
26
0
Order By: Relevance
“…Ostlund Farrants et al (1990), however, described induction of the branched-chain trihydroxicoprostanoylCoA oxidase by fatty diets in rodents. Phytanoyl-CoA hydroxylase activity was induced up to four times in cell lines grown in the presence of phytanic acid (Zomer et al 2000). In mouse liver, phytanic acid caused a differential induction of palmitate peroxisomal -oxidizing capacity (5-fold), of total catalase activity (only 1·5-fold) and urate or glycolate oxidase activities (no change).…”
Section: Discussionmentioning
confidence: 95%
“…Ostlund Farrants et al (1990), however, described induction of the branched-chain trihydroxicoprostanoylCoA oxidase by fatty diets in rodents. Phytanoyl-CoA hydroxylase activity was induced up to four times in cell lines grown in the presence of phytanic acid (Zomer et al 2000). In mouse liver, phytanic acid caused a differential induction of palmitate peroxisomal -oxidizing capacity (5-fold), of total catalase activity (only 1·5-fold) and urate or glycolate oxidase activities (no change).…”
Section: Discussionmentioning
confidence: 95%
“…The effect of elevated maternal phytanic acid on maternal or foetal outcomes in pregnancy has never been described. It has been postulated that phytanic acid does not cross the placenta (Zomer et al 2000) but clinical data is lacking. In this case it seems that elevated plasma phytanic acid that was not detrimental to the mother or foetus.…”
Section: Discussionmentioning
confidence: 99%
“…Phytanic acid (3,7,11,15-tetramethylhexadecanoic acid) is a methyl-branched fatty acid that originates from the phytol side of the chain of chlorophyll. Phytanic acid enters the human body in foods such as dairy products or other ruminant fats.…”
Section: Introductionmentioning
confidence: 99%
“…Pristanic acid can also activate PPARK [7]. We have recently reported that phytanic acid, when added to cell culture medium, is an activator of brown adipocyte di¡erentiation and transcription of the uncoupling protein-1 (UCP1) gene, the speci¢c marker of brown adipocytes [8].…”
Section: Introductionmentioning
confidence: 99%